Monitoring neutrophil elastase and cathepsin G activity in human sputum samples - Frey, Dario; Guerra, Matteo; Mall, Marcus A.; Schultz, Carsten (JoVE. Video journal, 2021)
Proteases are regulators of countless physiological processes and the precise investigation of their activities remains an intriguing biomedical challenge. Among the ~600 proteases encoded by the human genome, neutrophil serine proteases (NSPs) are thoroughly investigated for their involvement in the onset and progression of inflammatory conditions including respiratory diseases. Uniquely, secreted NSPs not only diffuse within extracellular fluids but also localize to plasma membranes. During neutrophil extracellular trap (NETs) formation, NSPs become an integral part of the secreted chromatin. Such complex behavior renders the understanding of NSPs pathophysiology a challenging task. Here, detailed protocols are shown to visualize, quantify and discriminate free and membrane-bound neutrophil elastase (NE) and cathepsin G (CG) activities in sputum samples.